Ab Initio Periodic Simulation of the Spectroscopic and Optical Properties of Novel Porous Graphene Phases - De La Pierre, Marco; Karamanis, P.; Baima, J.; Orlando, R.; Pouchan, C.; Dovesi, R. (American Chemical Society, 2013)
We present a detailed periodic ab initio quantum-mechanical simulation of two recently proposed systems, namely hydrogenated porous graphene (HPG) and biphenyl carbon (BPC), using hybrid HF-DFT functionals and all-electron Gaussian-type basis sets. The equilibrium geometry, the vibrational spectrum (including IR intensities), the full set of components of the polarizability and hyperpolarizability tensors are provided, the latter evaluated through a coupled-perturbed KS/HF scheme. IR and Raman spectra for the two systems are quite different, and differ also from graphene, thus permitting their experimental identification. It is then shown that small defects inserted into the graphene sheet lead to finite values for the in-plane components of the static (hyper) polarizability tensors, spanning a relatively large range of values. By dehydrogenation of porous graphene into biphenyl carbon, a noteworthy enhancement of the nonlinear optical properties through the static second dipole hyperpolarizability can be achieved. Vibrational contributions to the polarizability are negligible for both systems.